Cysteine-Altering NOTCH3 Variants Are Associated with an Increased Risk of Autoimmune Diseases - Rieder, Emily; Li, Jiang; Rodriguez-Flores, Juan L.; Taimur Malik, Muhammad; Abedi, Vida; Zand, Ramin (Journal of clinical medicine, 2023)
Autoimmune conditions have been reported among patients with cysteine-altering NOTCH3 variants and CADASIL. This study aimed to investigate the occurrence of autoimmune illnesses and markers of inflammation in such populations. Cases were identified who had a NOTCH3 cysteine-altering variant from the Geisinger MyCode® Community Health Initiative (MyCode®). We further performed external validation using the UK Biobank cohort. A cohort of 121 individuals with a NOTCH3 cysteine-altering variant from MyCode® was compared to a control group with no non-synonymous variation in NOTCH3 (n = 184). Medical records were evaluated for inflammatory markers and autoimmune conditions, which were grouped by the organ systems involved. A similar analysis was conducted using data from the UK Biobank (n~450,000). An overall increase in inflammatory markers among participants with a NOTCH3 cysteine-altering variant was observed when compared to an age- and sex-matched MyCode® control group (out of participants with laboratory testing: 50.9% versus 26.7%; p = 0.0047; out of total participants: 23.1% versus 10.9%; p = 0.004). Analysis of UK Biobank data indicated any autoimmune diagnosis (1.63 [1.14, 2.09], p= 2.665 × 10−3) and multiple sclerosis (3.42 [1.67, 6.02], p = 9.681 × 10−4) are associated with a NOTCH3 cysteine-altering variant in any domain. Our findings suggest a possible association between NOTCH3 cysteine-altering variants and autoimmune conditions.